2001
DOI: 10.1152/ajpheart.2001.280.3.h1113
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-independent, ouabain-sensitive relaxation of bovine coronary arteries by EETs

Abstract: Endothelium-derived hyperpolarizing factor (EDHF) is released in response to agonists such as ACh and bradykinin and regulates vascular smooth muscle tone. Several studies have indicated that ouabain blocks agonist-induced, endothelium-dependent hyperpolarization of smooth muscle. We have demonstrated that epoxyeicosatrienoic acids (EETs), cytochrome P-450 metabolites of arachidonic acid, function as EDHFs. To further test the hypothesis that EETs represent EDHFs, we have examined the effects of ouabain on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 43 publications
2
52
1
Order By: Relevance
“…Thus, the above studies are consistent with our observations that 11, 12‐EET may act as EDHF in the mesenteric vasculature obtained from control animals. As additional support for our observations, Prattet al 30. indicated that EETs might display similar behaviour to EDHFs.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, the above studies are consistent with our observations that 11, 12‐EET may act as EDHF in the mesenteric vasculature obtained from control animals. As additional support for our observations, Prattet al 30. indicated that EETs might display similar behaviour to EDHFs.…”
Section: Discussionsupporting
confidence: 90%
“…3 Furthermore, muscarinic receptor activation causes endothelium-dependent relaxation, EET synthesis, and SMC hyperpolarization in bovine coronary arteries. 19 ACh and BK cause endothelium-dependent hyperpolarization of coronary arterial SMCs by increasing K Ca channel activity, 4 and this can be abolished by TEA, charybdotoxin, or IBTx. 4,20 -23 There are other important K ϩ channels in the LIMA, including K v channels (inhibition of which depolarizes SMCs; Figure 6).…”
Section: K ؉ Channels and Edhfmentioning
confidence: 99%
“…EDHF-mediated vasodilation is blocked by the combined treatment with the Ca 2ϩ -activated K ϩ channel blockers charybdotoxin and apamin, and it is now generally believed that the blockade is due to inhibition of endothelial cell hyperpolarization and generation of the EDHF signal (12,17,19). Whereas there is evidence that epoxyeicosatrienoic acids (EETs) (5,26,44), potassium ions (3,19), and hydrogen peroxide (36) can act as an EDHF in some arteries, the identity of EDHF remains controversial and may differ among species and vascular segments (6,15,20,22,55).…”
mentioning
confidence: 99%